Perkutánní resení symptomatické masivní hepatikolitiázy po predchozím operacním výkonu s biliodigestivní anastomózou -- tri kazuistiky - Janousek, R; Danek, T; Vyhnálek, P; Hájek, J (Rozhledy v chirurgii, 2011)
PURPOSE: Presentation of our own experience with percutaneous treatment of symptomatic bile-duct stones like late complication in patients with biliodigestive anastomosis. METHOD: Three symptomatic female patients with biliodigestive anastomosis and acutely symptomatic with proven bile-duct stones above anastomosis were treated with initial percutaneous transhepatic drainage and later via percutaneous route using of endoscopic lithotryptor with special technique. RESULTS: All procedures were successful without complication, the patients are free of biliary symptoms in the long term. CONCLUSION: Percutaneous removal of bile-duct stones in patients with biliodigestive anastomosis is safe and effective method which can be used as an alternative to surgery.
Keywords: Gallstones; cholangiopankreatografie endoskopická retrográdní; střeva; Cholangiopancreatography, Endoscopic Retrograde; chirurgie žlučových cest; litotripse; Adult; Aged; dospělí; Biliary Tract Surgical Procedures; senioři; anastomóza chirurgická; lidé; Drainage; ženské pohlaví; Humans; Anastomosis, Surgical; drenáž; Intestines; Female; Lithotripsy; lidé středního věku; žlučové kameny; Middle Aged